PENGARUH KEMUDAHAN, KEAMANAN DAN PENGALAMAN PEMBELIAN TERHADAP KEPUTUSAN PEMBELIANSECARA ONLINEMENGGUNAKAN APLIKASI SHOPEE (Studi kasus mahasiswa Fakultas Ekonomi Universitas Maarif Hasyim Latif Sidoarjo) - Dewi, Nurna Dewi (Universitas Merdeka Madiun, 2019)
Abstrac This study aims to determine the effect of ease, security and purchase experience both partially and simultaneously on online purchasing decisions using the Shopee application. This research ia a survey research using questionnaire. The population selected in this study were students of Faculty of Economics, Maarif Hasim Latif University, Sidoarjo. The number of samples used was 91 respondents with purposive sampling method, which is based on the criteria of students who have made an online purchase using the Shopee application more than once. The results of the study found that: (1) Ease has a negative effect not significant on purchasing decisions with a value of Thitung equal to -1,941 <T table value 1,987 and significance level 0,056. (2) Security has a significant positive effect on purchasing decisions with a value of 2,784 and a significance level of 0.007. (3) Purchasing Experience has a significant positive effect on purchasing decisions with a Thitung value of 4.081 and a significance level of 0.000. (4) Ease, Security and Purchasing Experience simultaneously affect purchasing decisions with a Fcount value of 94.569> Ftable value of 2.71 and a significance level of 0.000. (5) the purchase experience variable is the dominant variable because it has the largest beta (β) coefficient value of 0.756. Key word : ease, safety, purchasing experience, online purchasing decisions